Efeito teratogênico do ditelureto de difenila, administrado durante a gestação em ratas e efeito de organocalcogênios sobre a reprodução em ratos machos - Stangherlin, Eluza Curte (2004)
Organochalcogens are important intermediates and the main applied reagents in organic synthesis and in industrial processes, which can increase human exposure risk to these chemicals in the workplace. The effects of single subcutaneous (s.c.) injection of diphenyl ditelluride ((PhTe)2) at days 6, 10 or 17 of gestation were evaluated in Wistar rats. No alterations were observed in maternal organism at the end of the experimental period. Maternal injections at day 10 of gestation resulted in appearance of malformation in the inferior and superior limbs, absent or short tail, subcutaneous blood clots, exophthalmia, hydrocephalus and exposed brain in fetuses on day 20 of gestation. Besides, (PhTe)2 reduced the fetal body and cerebral weight, kidneys length, measurements of body dimension and provoked 73% of fetal mortality. The administration of (PhTe)2 at day 17 of gestation induced appearance of hydrocephalus and evident edema in fetuses on day 20 of gestation. This administration caused 94% of fetal mortality and alterations at measurements of body dimension. Histological evaluations demonstrated alterations in GD10 and GD17. Thus, (PhTe)2 can be teratogenic to the rat fetuses. The two last fetal periods of development in the rat are the critical periods for induction of anomalies induced by (PhTe)2. Other focus of this study was the evaluation of effect of organochalcogens on the fertility and reproductive system of male rats. Adult male rats were exposed acutely (single dose) to diphenyl diselenide ((PhSe)2 and diphenyl ditelluride prior to mating. Clinical signs of toxicity following administration of drug were evidenced for reduction of body weight of rats. However, eight days after compounds exposure the mating and fertility indices were not affected in treated groups. A number of biochemical parameters in rat testes were examined, such as δ-aminolevulinic acid dehydratase (δ-ALA-D) activity, lipid peroxidation, glycogen content and components of the antioxidant defenses (superoxide dismutase (SOD) activity and ascorbic acid concentration). Except for a decrease in testes glycogen content on (PhSe)2-treated group, no alterations were found on treated groups. Histological evaluation revealed that no modification were found on the testicular tissue after drugs administration. Based on these results, there was no observed reproductive toxicity in male Wistar rats exposed acutely to (PhTe)2 and (PhSe)2.